Pengaruh Bimbingan Belajar Online (Ruangguru) dan Minat Belajar Terhadap Hasil Belajar Ekonomi Kelas X di SMA Negeri 3 Padang - Meizi Syafri Yendi; Annur Fitri Hayati (Universitas Negeri Padang, 2020)
This study aims to reveal the Effect of Online Tutoring (Ruangguru) and Learning Interests on Economic Learning Outcomes of Class X Students in SMA N 3 Padang. This research is an Associative Descriptive with a Quantitative approach. The population in this study amount of class X students in SMA N 3 Padang who took Bimbel Online (Ruangguru), which totaled 135 person. The sampling technique uses a proportional random sampling technique which amounts to 58 people. The data is obtained through a questionnaire using a Likert scale that has been tested for validity and reliability. Data analysis techniques used are descriptive analysis and inductive analysis. For testing the hypothesis that is t test and f test. Based on the results of t-test hypotheses the influence of online tutoring (Ruangguru) on learning outcomes is influential and positive on economic learning outcomes, t-test students' learning interest has an effect and negative on economic learning outcomes. While the f test simultaneously influences online tutoring (Ruangguru) and interest in learning towards economic learning outcomes. The magnitude of the influence of online tutoring (Ruangguru) and interest in learning towards economic learning outcomes is 11% and the remaining 89% is influenced by other variables not included in this research model. Keywords: bimbel, minat belajar, hasil belajar, ruangguru